NEONATAL OMPHALITIS IS STILL COMMON IN EASTERN TURKEY - GUVENC, HY; GUVENC, M; YENIOGLU, H; AYATA, A; KOCABAY, K; BEKTAS, S (Scandinavian University Press, 1991)
88 newborns with omphalitis diagnosed at a University Hospital in Eastern Turkey from January 1988 to December 1990 were reviewed. The yearly incidence was 7.7% in inpatient newborns. Risk factors including septic delivery (especially home delivery), prematurity, and being small for gestational age appeared to be important. Clinical manifestations, white blood cell and absolute neutrophil counts were non-specific and non-pathognomonic. Bacteriologic analysis revealed that Gram-positive bacteria (68%) predominated over Gram-negative isolates (60%). Staphylococcus aureus and Escherichia coli were the most frequent microorganisms. Mortality rate was 15%; all deaths occurred in patients presenting with systemic symptoms. The following poor prognostic factors were identified: septic delivery (particularly at home), prematurity, being small for gestational age and the development of systemic symptoms.
Keywords: Newborn